MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Ushalihah, Annisa; Aeni, Ani Nur; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The ability of mathematical understanding among elementary school students is still low one of them on geometry material some students still find it difficult. As an alternative to improve the ability of mathematical understanding of RME approach. The RME approach is a learning that uses concrete objects toward abstract concepts, or learning can use shadows. The research method used experiments with pretest and postest group design. The population in the study were elementary school students in Rancakalong sub-district with the sample of SDN Pasirbenteng II as the experimental class and SDN Pasirbiru as the control class. The results of the research that the RME approach can improve the ability of mathematical understanding, the enhancement of the mathematical ability of conventional learning can be categorized similarly with RME learning, through RME approach the students give positive responses to the learning of mathematics, and the supporting factors are group learning and media help students understand the concept while the factors The inhibitor is not yet used to learning with RME and less management of the class.Â